LIFE AND GLORY OF VLADIMIR IVANOVICH VERNADSKY - Minenko, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Article is devoted to the 150 anniversary from the date of a birth of the outstanding scientific geologist, the naturalist and the thinker which fruitfully worked in the field of a crystallography, to geology, soil science, chemistry, biology, radiology, the doctrine about minerals, meteoritics, stories of a science, history of philosophy, history of Slavs, the organizations of scientific researches, higher education problems etc. to Its knowledge was close within the limits of modern to it of sciences. The scientist has much more outstripped in the works not only the time, but even ours. In article the biographic facts from its scientific and organizational activity, and also a number of its interesting definitions are mentioned.